2023
DOI: 10.1002/admt.202301415
|View full text |Cite
|
Sign up to set email alerts
|

Packaged Elastomeric Optical Fiber Sensors for Healthcare Monitoring and Human‐Machine Interaction

Zhenhua Zhang,
Lei Zhang

Abstract: Elastomeric polymer optical fiber (EPOF) enabled flexible optical sensors have been attracting intensive research interest due to their excellent stretchability, sensing performance, and anti‐electromagnetic interference. However, a soft EPOF without effective protection tends to be damaged, which may undermine its long‐term stability, and thus, limit its practical applications. In this work, a strategy for packaging a section of EPOF is proposed, a light‐emitting diode (LED), and a photodiode (PD) into a stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…It is found that the sensor is not quite sensitive to a small bending angle < 20 • , which can be attributed to the large numerical aperture (0.5) of POF and the small gap distance [20]. In the linear bending response range (30-60 • ), the derived sensitivity is −2.1%/ • and is comparable to the recently reported soft fiber sensors [20,22]. The bending sensitivity can be improved by simply tuning the air gap distance, although the effective angle range detection can be compromised [20].…”
Section: Quantification Of Pof Sensors To Mechanical Deformationssupporting
confidence: 64%
See 2 more Smart Citations
“…It is found that the sensor is not quite sensitive to a small bending angle < 20 • , which can be attributed to the large numerical aperture (0.5) of POF and the small gap distance [20]. In the linear bending response range (30-60 • ), the derived sensitivity is −2.1%/ • and is comparable to the recently reported soft fiber sensors [20,22]. The bending sensitivity can be improved by simply tuning the air gap distance, although the effective angle range detection can be compromised [20].…”
Section: Quantification Of Pof Sensors To Mechanical Deformationssupporting
confidence: 64%
“…As shown in Figure 2a, the normalized transmitted light intensity significantly decreases with increasing strain, and the repeatability is reasonably good for practical applications. We define strain sensitivity as S = ∆I/ε, where ∆I is the change in normalized intensity and ϵ is the change in strain [17,22]. Thus, the extracted strain sensitivity is approximately −0.2.…”
Section: Quantification Of Pof Sensors To Mechanical Deformationsmentioning
confidence: 99%
See 1 more Smart Citation